Analisis Manajemen Inventory dengan Metode Economic Order Quantity (EOQ) Studi pada Toko Bangunan Cahaya Terang - Putra, Maulana Daniel; Habriyanto, Habriyanto (ARZUSIN, 2025)
Ineffective inventory management at Toko Bangunan Cahaya Terang has led to imbalances between demand and product availability, potentially increasing operational costs and the risk of lost sales. This study aims to analyze inventory management using the Economic Order Quantity (EOQ) method to determine the optimal order quantity, ordering frequency, safety stock, and reorder point for five types of building material products. A descriptive quantitative method was employed, with data collected through observation, interviews, and secondary data analysis. Data analysis was conducted using EOQ calculations to optimize inventory management. The results show that applying the EOQ method significantly reduces ordering frequency and storage and ordering costs. By using this method, Toko Bangunan Cahaya Terang can enhance inventory management efficiency, reduce stockout risks, and maximize operational profits. The study concludes that the EOQ method is an effective tool for addressing inventory issues, offering practical solutions to stock imbalances, and supporting overall improvement in store operational performance.